Immunomodulatory Effects of Ethanol Extract of Lime Peel on Phagocytosis Activity and Delayed-Type Hypersensitivity Response - Amanda, Safina Audiva; Yuandani, Yuandani (Newinera Publisher, 2024)
The natural human environment is inhabited by various organisms, including those harmful to the body such as bacteria, viruses, fungi, and other pathogens. This condition weakens the immune system's response to pathogens, making the body more susceptible to diseases such as rheumatoid arthritis, cancer, and other inflammations. In some cases, this condition can be fatal, leading to death. This study aims to examine the immunomodulatory effects of Ethanol Extract of Lime Peel on phagocytosis activity and delayed-type hypersensitivity response in experimental animals. The research methods include sample collection and processing, plant identification, extract preparation, and immunomodulatory effect testing. Phytochemical screening results showed the presence of alkaloids, glycosides, flavonoids, tannins, and steroids in the extract of the lime peel. Simplicia and ethanol extract of lime peel characterization yielded results meet the standards of the Indonesian Herbal Pharmacopoeia 2nd edition. Immunomodulatory effect testing was conducted through phagocytosis activity and delayed-type hypersensitivity response assays. The results showed that the extract at doses of 25, 50, and 100 mg/kgBW had immunostimulatory effects in enhancing phagocytosis activity, while doses of 17.5 mg/kgBW, 35 mg/kgBW, and 70 mg/kgBW significantly increased delayed-type hypersensitivity response compared to the negative control. These findings indicate the potential of ethanol extract of Citrus aurantifolia as an immunomodulator that can enhance the body's immune system. This study provides an important contribution to the development of immunomodulatory therapy derived from natural ingredients such as lime peel for managing immunity-related diseases with lower side effects.